Literasi Keuangan Syariah bagi Siswa Siswi Madrasah Tarbiyah Islamiyah (MTI) Dan SMA Pembina Bangsa, Bukitinggi, Kabupaten Agam, Sumatra Barat - Raflis, Ratnawati; Rahmaita, Rahmaita; Arita, Enny; Nini, Nini; Sovita, Ingra; Maryanti, Eka (LPPM Universitas Dharma Andalas, 2024)
Indonesia has the potential to become a sharia financial and economic center at regional and global levels. Education related to sharia economics and finance has been carried out by Bank Indonesia, the Financial Services Authority, the Ministry of Religion and the Ministry of Education and Culture through their respective work units. However, this education has not touched more basic units such as families and individuals. According to OJK data, sharia financial literacy in Indonesia is still in the very low category. One of the causes of Sharia financial literacy is because the Indonesian Muslim population cannot directly experience the positive economic and financial impacts of Sharia. The fourth phase in Sharia economic and financial literacy material starts from the age of 16 to the age of 18 or the period of high school level education in Indonesia. This phase is the phase of learning advanced knowledge of Sharia economics and finance accompanied by practical training. It is hoped that this age group will be trained to have the ability to manage the economy and finances according to sharia. Therefore, we hope to increase the knowledge and understanding of high school level students, namely Madrasah Tarbiyah Islamiyah and Pembina Bangsa High School students regarding Sharia Finance so that it can be practiced in everyday life.